Prognostic Role of Platelet-to-Lymphocyte Ratio in Patients With Bladder Cancer: A Meta-Analysis - Wang, Xingmu; Ni, Xiaoyan; Tang, Guiliang (Frontiers in Oncology, 2019)
Background: Many studies have been reported that platelet-to-lymphocyte ratio (PLR) may be associated with the prognosis of bladder cancer, but the results are inconsistent. Therefore, we performed a meta-analysis to evaluate the effect of pretreatment PLR on the prognosis of bladder cancer. Methods: The databases PubMed, Embase, Cochrane Library, and Web of Science were searched. Pooled hazard ratios (HRs) and 95% confidence intervals (CIs) were used to analyze the relationship between PLR and prognosis. Pooled odds ratios (ORs) and 95% CIs were used to analyze the relationship between PLR and clinicopathological features. Publication bias was estimated using Begg’s funnel plot asymmetry tests. Results: A total of 8 studies comprising 3303 patients were included in this meta-analysis. An elevated PLR was significantly associated with poorer overall survival (OS) (HR=1.26, 95% CI= 1.03- 1.54, p=0.026), but not with cancer-specific survival (CSS) (HR=1.15, 95%CI=0.95-1.38, p=0.149) or recurrence-free survival (RFS) (HR=1.72, 95%CI=0.79-3.75, p=0.175). In addition, high PLR was correlated with age≥65 years (OR=1.82, 95%CI=1.24-2.67, p=0.002), whereas was not significantly correlated with sex, tumor grade, tumor stage, distant metastasis, or tumor size. Conclusions: The pretreatment PLR could serve as a predicative biomarker of poor prognosis for patients with bladder cancer.